Loudspeakers Optional: A history of non-loudspeaker-based electroacoustic music. Issue 2 (12th July 2017) - Long, Jason; Murphy, Jim; Carnegie, Dale; Kapur, Ajay
Abstract : The discipline of electroacoustic music is most commonly associated with acousmatic musical forms such as tape-music and musique concrète, and the electroacoustic historical canon primarily centres around the mid-twentieth-century works of Pierre Schaeffer, Karlheinz Stockhausen, John Cage and related artists. As the march of technology progressed in the latter half of the twentieth century, alternative technologies opened up new areas within the electroacoustic discipline such as computer music, hyper-instrument performance and live electronic performance. In addition, the areas of electromagnetic actuation and musical robotics also allowed electroacoustic artists to actualise their works with real-world acoustic sound-objects instead of or along side loudspeakers. While these works owe much to the oft-cited pioneers mentioned above, there exists another equally significant alternative history of artists who utilised electric, electronic, pneumatic, hydraulic and other sources of power to create what is essentially electroacoustic music without loudspeakers. This article uncovers this 'missing history' and traces it to its earliest roots over a thousand years ago to shed light on often-neglected technological and artistic developments that have shaped and continue to shape electronic music today.